Chromosome-level genome assembly provides new insights into Japanese chestnut (Castanea crenata) genomes - Wang, Jiawei; Hong, Po; Qiao, Qian; Zhu, Dongzi; Zhang, Lisi; Lin, Ke; Sun, Shan; Jiang, Shuna; Shen, Bingxue; Zhang, Shizhong; Liu, Qingzhong (Frontiers in Plant Science, 2022)
Japanese chestnut (Castanea crenata Sieb. et Zucc) is an economically and ecologically important chestnut species in East Asia. Here, we presented a high-quality chromosome-level reference genome of the Japanese chestnut cultivar ‘Tsukuba’ by combining Nanopore long reads and Hi-C sequencing. The final assembly has a size of 718.30 Mb and consists of 12 pseudochromosomes ranging from 41.03 to 92.03 Mb, with a BUSCO complete gene percentage of 97.6%. A total of 421.37 Mb repetitive sequences and 46,744 gene models encoding 46,463 proteins were predicted in the genome. Genome evolution analysis showed that Japanese chestnut is closely related to Chinese chestnut, and they shared a common ancestor ~6.5 million years ago. This high-quality Japanese chestnut genome represents an important resource for the chestnut genomics community and will improve our understanding of chestnut biology and evolution.